Heat transfer enhancement around a finned vertical antenna by means of porous media saturated with Water-Copper nanofluid. (December 2021) - Martin, E.; Sastre, F.; Velazquez, A.; Baïri, A.
Abstract: Combination of porous media and nanofluids is used to improve heat transfer around a vertical finned cylindrical antenna generating high heat flux. This technique ensures correct operation of this electronic device under the conditions recommended by the manufacturers. This active component is enclosed inside another concentric quasi-cylindrical cavity maintained at low temperature. Cooling is carried out via highly porous materials of various thermal conductivities, saturated with Water-Copper nanofluid whose volume fraction varies between 0% (pure water) and 5%. Natural convective heat transfer is quantified by means of the average Nusselt number. A new Nusselt-Rayleigh correlation is proposed in the 2.53 × 10 5 to 5.13 × 10 7 Rayleigh number range. The ratio between the conductivity of the porous material and that of the water (base fluid) was varied between 4 and 41.2. The results obtained show that, as compared to the reference case (pure water as the working fluid, and no porous media present), Nusselt number improvements of up to 65% can be obtained in the upper limit region of the span of Rayleigh numbers considered. This study has been performed via a numerical approach based on the volume control method using the SIMPLE algorithm. Highlights: Thermal control of an antenna with power electronics. Nanofluid combined with porous media. Nusselt number correlation for a range of governing parameters. Thermal engineering design guidelines.